Pengelolaan Sarana Dan Prasarana Laboratorium Ipa Di MTs YPK Cijulang - Alfiyatun; Imas Patmawati; Dyah Ayuningtias; Gita Puspita; Nurjamaludin; Yayat Hidayat (Jurnal Pendidikan Sosial Dan Konseling, 2024)
Research conducted at MTs YPK Cijulang, this research uses qualitative approach method. Discusses the management of science laboratory facilities and infrastructure at MTs YPK Cijulang. The purpose of this study is to determine the management of facilities and infrastructure at MTs YPK Cijulang. Where the management of educational facilities and infrastructure is procurement and utilization to support optimal learning activities. And Infrastructure is an important part of educational institutions and is one of the 8 national standards of education. Based on the results of research in the management of laboratory facilities and infrastructure at MTs YPK Cijulang has carried out the process of planning, maintenance and elimination. From one such process, the process planning, maintenance and elimination. From one of these processes, the maintenance process is the most important thing in the management of educational facilities and infrastructure. Because, the process can affect the continuity of student learning / practicum activities.